Implikasi Ketatanegaraan Presidential Term Limit menurut Pasal 7 UUD NRI 1945 sebelum Amendemen terhadap Presidential Continuism Masa Orde Baru - Moch Chafid; Anna Erliyana (Journal of Judicial Review, 2021)
Presidential term limit according to Article 7 of the 1945 Constitution (UUD) before the amendment should not be interpreted as only one measure namely in terms of quantity (limits on the term of office and the maximum period of office in office), but must regulate in terms of quality (legal norms and political ethics in commitment creating a democratic and competent government). As a result, every President in power will endeavor to presidential continuation by changing, avoiding, reinterpreting, amending the constitution or even presidential term limit in article 7 of the 1945 Constitution before the amendment. In the constitutional order, it will have implications for every President in power to form an authoritarian government and reduce democracy, abuse of the President's power to hold office continuously, give birth to an elected president who is incompetence in government administration, and creates stagnation of political regeneration.